A Study on Service Quality, Tourist Value Perception, and Destination Image for Revisit Intention in Lombok - Wahim, Isdar; Hamzah, Muhammad (Politeknik Pariwisata NHI Bandung, 2024)
This study seeks to assess the impact of service quality, perceived value, and destination image on tourists' intention to return to Lombok. Based on a study involving 366 respondents, the research confirmed the significant relationship between these variables, with tourists generally expressing high satisfaction during their visits, particularly in group settings. Empathy emerged as the most influential dimension within service quality, while emotional value was a key aspect of perceived value. The resulting image dimension strongly influenced the destination image, indicating that Lombok leaves a lasting and positive impression on visitors. The analysis revealed that both service quality and destination image significantly influence tourists' intentions to revisit, while perceived value did not exhibit a significant effect. The findings imply that enhancing emotional and empathetic service aspects, along with strengthening Lombok’s positive image, could effectively encourage repeat visits. However, since perceived value alone does not drive revisit intention, the study suggests that other factors may play a more critical role. This study recommends tourism stakeholders in Lombok concentrate on enhancing service quality, especially in empathy, and persist in enhancing the island's image through focused marketing strategies. Future research should explore additional variables that influence the intention to revisit in order to provide a more comprehensive understanding of tourist behavior.